Killing commendatore ebook A novel. - Murakami, Haruki (2018)
NATIONAL BESTSELLER • A tour de force of love and loneliness, war and art—from one of our greatest writers. • “Exhilarating ... magical.” — The Washington Post When a thirty-something portrait painter is abandoned by his wife, he secludes himself in the mountain home of a world famous artist. One day, the young painter hears a noise from the attic, and upon investigation, he discovers a previously unseen painting. By unearthing this hidden work of art, he unintentionally opens a circle of mysterious circumstances; and to close it, he must undertake a perilous journey into a netherworld that only Haruki Murakami could conjure.